Review on phytopharmacological activities of andrographispaniculata (burm.f) nees. - S.ELUMALAI; R.BANUPRIYA; T. SANGEETHA; S. MADHUMATHI (International Journal of Pharma and Bio Sciences, 2016)
Medicinal plants are in prevalence from the origin of the earth which has been efficiently used by ancient people as a cure for various ailments. The plant extracts are identified and act as an important source of active ingredient and secondary metabolite products such as alkaloid, terpenoids, which is used in curing diseases, for drug production and perpetuating good health by both the traditional and orthodox medical practitioners. The current aim of this review is to accumulate the morphological and pharmacological applications of Andrographis paniculata as a multipurpose drug showing efficient activity in curing various diseases. The plant is highly useful in curing various health ailments of human beings especially in viral diseases such as respiratory problems, HIV, Liver damage etc. The phytochemical tests revealed the presence of glycosides, saponins, tannins and alkaloids, but not of anthraquinones. Thus the plant has an important compound named as Andrographolide, a diterpenoid lactone having a diversity of pharmacological effects. The overdosage of the plant leads to some side effects like nausea, vomiting and loss of appetite Therefore, researchers have to perform various formulation for A. paniculata and develop a new drug molecules. The plant is to be widely cultivated and farmers should be encouraged in cultivating the medicinal plant which has multifarious therapeutic uses. The plant is considered as a safe, highly important medicinal plant for mankind.